Application of Marketing Mix Variables (4P's) in the University Libraries in Kerala - Suresh Kumar, P.K. (Journal of Information and Knowledge, 2013)
Marketing is beneficial to libraries because an effective marketing programme can help the library to create competitive advantage through the development of new services or changes of the existing ones to satisfy their users better; improvement of their organizational status and image to different stakeholders; and there by improve their performance in general This paper attempts to study the application of marketing mix variables (4P's), the degree of marketing orientation and the users attitude towards the marketing applications of the university libraries in Kerala The data for the study collected from a sample of 842 users of the university libraries in Kerala such as Kerala University Library (KUL), Mahatma Gandhi University Library (MGUL), Cochin University of Science and Technology Library (CUSATL) and CH Mohammed Koya Library of University of Calicut (CHMKL). The study found that university libraries in Kerala have moderate degree of marketing orientation with respect to the marketing mix variables. It is indeed in the university libraries in Kerala to initiate new information services and products suitable for the different user groups. From the analysis of the marketing elements viz. product, place, price and promotion, it is observed that university libraries in Kerala needs better promotional activities. A separate marketing division with skilled staff with a marketing plan is desirable to make the marketing activities more efficient and effective.